2017
DOI: 10.1007/s11250-017-1292-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rumen-protected choline additive to diet on productive performance of male Zaraibi growing goats during hot summer season in Egypt

Abstract: Twenty Zaraibi goat bucks were used in this experiment which lasted 3 months during summer season of Egypt. The animals were divided randomly into two equal groups. The first group was kept without treatment as control while in the second group, rumen-protected choline (RPC) at the level of 20 g/buck/day was added to the concentrate feed mixture at the morning feeding. RPC additives to diet of Zaraibi goat bucks during the period of hot summer season increased (P < 0.01) total gain and average daily gain compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 14 publications
12
27
1
Order By: Relevance
“…In the present study, any effect of RPC supplementation on AST and ALT was found, indicating that the goats were in good health. This result was consistent with the findings of Habeeb et al (2017), who did not observe any effect of RPC supplementation on plasma AST and ALT in growing male Zaraibi goats. Serum urea nitrogen is an important indicator of nitrogen metabolism in the body.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, any effect of RPC supplementation on AST and ALT was found, indicating that the goats were in good health. This result was consistent with the findings of Habeeb et al (2017), who did not observe any effect of RPC supplementation on plasma AST and ALT in growing male Zaraibi goats. Serum urea nitrogen is an important indicator of nitrogen metabolism in the body.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of RPC was greater when supplemented in low-energy diets. A similar response was observed by Habeeb et al (2017), who reported the best growth, feed conversion, blood metabolite levels and economic efficiency in Zaraibi goats fed diets supplemented with RPC, particularly subjected to heat stress during the Egyptian summer. We assumed that RPC supplementation may have a greater effect under stress conditions, such as high temperature or low dietary energy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Bryant et al (1999) observed that ADG improved with 2.5 g/kg DM RPC in the diet of lambs, but there was no response at higher levels (5 and 10 g/kg DM). The addition of choline chloride in RPC at lower dietary concentrations in beef cattle and goats improved feed conversion and ADG (Pinotti et al, 2009;Habeeb et al, 2017). However, when choline was combined with RPC the productive performance was impaired (El-Gendy et al, 2012) or showed no response in daily gain (Rodríguez-Guerrero et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ruminally protected choline chloride has been the most frequently evaluated source of choline for small ruminants (Bryant et al, 1999;Godinez-Cruz et al, 2015;Tsiplakou et al, 2016;Habeeb et al, 2017), and doses above 2.5 g/kg DM, equivalent to an intake of over 3 g/d for lambs, showed adverse effects on lamb performance (Li et al, 2015). However, the causes of the impaired performance have not been identified.…”
Section: Introductionmentioning
confidence: 99%